Peripheral serotonin lacks effects on endothelial adhesion molecule expression in acute inflammation. (8th October 2021) - Mauler, Maximilian; Schanze, Nancy; Krauel, Krystin; Schoenichen, Claudia; Glatzki, Franziska; Poeschl, Susanna; Stallmann, Daniela; Mezger, Julius; Gauchel, Nadine; Sharipova, Diana; Rieder, Marina; Hilgendorf, Ingo; et al.
Abstract: Background: Peripheral, non‐neuronal serotonin promotes the recruitment of neutrophils to sites of acute inflammation and tissue damage. Direct effects of serotonin on neutrophil function were shown to be involved. However, the influence of serotonin on the endothelial counterpart is unknown. Objectives: To investigate whether serotonin alters the function of endothelial cells in leukocyte recruitment during acute inflammation. Methods: We used two murine models of acute inflammation: intraperitoneal lipopolysaccharide (LPS) injection and mesenteric ischemia/reperfusion injury (I/R). To study effects of peripheral serotonin, leukocyte recruitment and endothelial adhesion molecule expression were compared in wild type (WT) and tryptophan hydroxylase 1 deficient ( Tph1 −/− ) mice, which are unable to synthesize peripheral serotonin. Results: As expected, neutrophil transmigration into the peritoneal cavity following LPS injection was impaired in Tph1 −/− mice. Abdominal blood vessels, however, showed no difference in adhesion molecule expression. In the early reperfusion phase after mesenteric I/R, the number of rolling leukocytes was significantly lower in Tph1 −/− compared to WT. In line with the LPS model, endothelial adhesion molecule expression was independent of serotonin. In vitro experiments using human umbilical vein endothelial cells (HUVECs) confirmed that serotonin does not affect endothelial adhesion molecules. Conclusions: The inflammatory release of peripheral serotonin is dispensable for the regulation of endothelial adhesion molecules.